Rancang Bangun Back-End Aplikasi HaePe untuk Penjadwalan Tugas Rumah Tangga Berbasis REST API - Hanhan Hanafiah Solihin; Mochamad Rizki Pratama Suhernawan; Herna Gunawan; Dayanni Vera Versanika (LPPM STMIK Bandung, 2025)
According to the Survei Angkatan Kerja Nasional (SAKERNAS) in August 2020, 69.52% of female workers who are married, with 34.41% of them working more than 40 hours per week, are potentially exposed to work-family conflict. Married women or mothers tend to experience such conflict due to the dual demands of professional and domestic roles. Literature indicates that one of the primary factors contributing to work-family conflict is time constraints caused by both professional work and household responsibilities. Other studies have shown that this conflict intensifies when one partner feels they bear a disproportionate share of domestic work compared to their spouse. In response to this issue, this study designs a task scheduling application named HaePe, aimed at helping married couples and other family members distribute household tasks fairly based on individual routines and habits. The application is developed for the Android platform and supported by an API service that manages data and integrates with third-party services such as Google. The API is designed using the Representational State Transfer (REST) architecture to facilitate code implementation and management. Functionality testing is conducted using the black-box method to ensure that the services operate as intended. This study is expected to serve as a reference for implementing REST-based API services to support digital solutions for household task management.